2016
DOI: 10.1515/aep-2016-0028
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of naphthalene biodegrading Methylobacterium radiotolerans bacterium from the eastern coastline of the Kingdom of Saudi Arabia

Abstract: Bioremediation is based on microorganisms able to use pollutants either as a source of carbon or in co-metabolism, and is a promising strategy in cleaning the environment. Using soil contaminated with petroleum products from an industrial area in Saudi Arabia (Jubail), and after enrichment with the polycyclic aromatic hydrocarbon (PAH) naphthalene, a Methylobacterium radiotolerans strain (N7A0) was isolated that can grow in the presence of naphthalene as the sole source of carbon. M. radiotolerans is known to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 37 publications
(39 reference statements)
0
16
0
Order By: Relevance
“…This study also showed that the increase in BaP concentration is associated with a decrease in 10BZ1A growth, which is consistent with previously reported studies. This includes anthracene using Bacillus licheniformis [34], and a co-culture of Ralstonia pickettii and Thermomonas haemolytica [28]; phenanthrene on a co-culture of Pseudomonas citronellolis and S. maltophilia [28]; anthracene and pyrene on Ochrobactrum sp. [25]; pyrene on Achromobacter xylosoxidans, and on the halophilic strains of Halomonas shengliensis and Halomonas smyrnensis [27,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also showed that the increase in BaP concentration is associated with a decrease in 10BZ1A growth, which is consistent with previously reported studies. This includes anthracene using Bacillus licheniformis [34], and a co-culture of Ralstonia pickettii and Thermomonas haemolytica [28]; phenanthrene on a co-culture of Pseudomonas citronellolis and S. maltophilia [28]; anthracene and pyrene on Ochrobactrum sp. [25]; pyrene on Achromobacter xylosoxidans, and on the halophilic strains of Halomonas shengliensis and Halomonas smyrnensis [27,35].…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, bacteria DNA was extracted and purified using Qiagen Powerfecal Kit (Hilden, Germany), following the user's manual. The resulting purified DNA was subjected 16S rRNA gene amplification by PCR and sequencing, as described previously [28]. Around 1400 base pairs of 16S rRNA gene was amplified using Primers 27F AGAGTTTGATCMTGGCTCAG and 1492R CGGTTACCTTGT TACGACTT, and then sequenced using the primers 518F: CCAGCAGCCGCGGTAATACG and 518R: GTATTACCGCGGCTGCTGG, a Big Dye terminator cycle sequencing kit (Applied Bio-Systems, USA), and an automated DNA sequencer (Applied BioSystems model 3730XL, USA).…”
Section: Species Identificationmentioning
confidence: 99%
“…Interestingly, so far, the two systems, CYP153 and AlmA, have not been reported in thermophilic bacteria degrading n-alkanes. Instead, these thermophiles express a novel type of alkane monooxygenase system, LadA, which was initially discovered in a G. thermodenitrificans NG80-2 strain [32,33] Study ST30 identified protocatechuic acid, and so far, the existence of this metabolite has not yet been identified in mesophiles, although it has been proposed [78].…”
Section: N-alkanesmentioning
confidence: 99%
“…Members of the Rhizobiales as well as Frankiales are well known as nitrogen-fixing symbionts associated with plant roots 55 , and free-living members of the Rhizobales are also thought to catalyze nitrogen fixation in a variety of ecosystems 56 . Methylobacterium was shown to grow on PAHs as well as produce biosurfactants in oil-contaminated systems 57,58 . Recently, it was shown that Frankia grows with PAHs as the sole carbon source and contains genes for alkane degradation 59 .…”
Section: Resultsmentioning
confidence: 99%